Age-defying swallowing - Palacio, María-Itatí; Bermejo, Rosa-María; Lucas-Ochoa, Ana-María; González-Cuello, Ana-María; Fernández-Villalba, Emiliano; Herrero, María-Trinidad (Frontiers in Aging, 2025)
Swallowing disorders, which are generally underdiagnosed, affect the elderly, leading to a decreased quality of life and complications, including aspiration pneumonia and death. Understanding the neurophysiology of swallowing and the causes of its dysfunction is a fundamental tool for the prevention, early diagnosis, and treatment of dysphagia. New technologies open a wide range of possibilities for the implementation of new care protocols for this disorder.